A quasi-wireless intraoperatory neurophysiological monitoring system - Alonso Rivas, Eduardo; Giannetti, Romano; Rodríguez-Morcillo García, Carlos; Matanza Domingo, Javier; Muñoz Frías, José Daniel; Scandurra, Graziella; Ciofi, Carmine; Vega Zelaya, Lorena; Pastor, Jesús (My University)
Intraoperative Neurophysiological Monitoring is a set of monitoring techniques that reads electrical activity generated by the nervous system structures during surgeries. In non-trivial surgeries, neurophysiologists require a significant number of electrical signals to be picked up to check the effects of the surgeon’s actions in real time or to confirm that the correct nerves are selected. As a result, cabling the patient in the operating room can become cumbersome. The proposed WIONM module solves part of the problem by converting a good part of those cables into a wireless connection that is substantially transparent to the human operator and the existing medical instrumentation.
Artículos en revistas
Keywords: Instituto de Investigación Tecnológica (IIT)